Comparative in vitro rumen fungal degradation and gas production of cellulosic feeds in cattle and buffalo - SANGWAN, D C; KUMAR, SHIV; BHATIA, S K; SINGH, SADHANA (The Indian Journal of Animal Sciences, 2014)
Ruminal degradations (in vitro) of DM and fibrous components in 9 substrates, besides gas production profile by anaerobic fungi which were compared in cattle and buffalo were influenced (P<0.01) by cell wall structural carbohydrates and varied between cattle and buffalo. Cattle excelled (P<0.01) buffalo fungi in fermenting DM of substrates, which corroborated the pattern on ruminal gas production volume. The overall NDF disappearances among feedstuffs differed (P<0.01) but remained alike owing to the source of rumen fungi. Least NDF and ADF degradations from paddy straw, pearlmillet slover and sugarcane bagasse corresponded to rumen gas production volumes. However, fibrous moieties of hays were maximally degraded by both ruminant fungi, though, magnitude of ADF disappearances (96 hr relative to 12 hr) exceeded (P<0.01) in buffalo than cattle for berseem and oat hay. The selective ruminant species (superiority of cattle than buffalo) response in degrading (P<0.01) cellulose from only 4 substrates was evidently discerned. These differential rumen fungi degradations may sequentially pinpoint and reflect in feed dry matter consumption and rumen fill.